PENGARUH PENGOLAHAN TANAH DAN TAKARAN PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG SEMI (Zea mays L.) - Dian Murti Minangsih; Putro Hairutomo Setiko (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2021)
This study aims to determine the effect of soil cultivation and nitrogen fertilizer dosage on the growth and yield of maize (Zea mays L.). This study used an experimental method with a Split Plot Design using 2 factors, namely soil cultivation (P) as the main plot consisting of 3 levels, namely p0 (without soil cultivation), p1 (minimum soil cultivation), p2 (perfect soil cultivation. ). The dose of nitrogen fertilizer (N) as subplots consists of 3 levels, namely n0 (0 kg ha-1 N), n1 (90 kg ha-1 N) and n2 (180 kg ha-1 N). The results showed: 1) there was an interaction between soil cultivation and nitrogen fertilizer dosage on plant height at 4 and 6 MST, and ear length, where complete soil treatment and nitrogen fertilizer dosage of 180 kg / ha (p2n2) gave the best results. 2) The effect of independent soil treatment and nitrogen fertilizer dosing on the observation of plant height at 5 WAP, and number of leaves at 4.5 and 6 WAP. The best results were found in p2 (Perfect Soil Treatment) and n2 (180 kg ha-1 N) treatments.